Profound Importance of Cyber security in the Field of Business - Abdumalikov, Giyosiddin (International Journal of Human Computing Studies, 2022)
Cyber security refers to the safeguarding of the systems which are connected to the Internet including hardware, software, and data, from cyber threats. Individuals and businesses utilize the method to prevent illegal access to data centers and other digital systems. A robust cyber security strategy can give a good security posture against hostile attacks aimed at gaining access to, altering, deleting, destroying, or extorting critical data from an organization's or user's systems. Cyber security is also important in avoiding attacks that try to disable or impair the operation of a system or device (Shea and S. Gillis, 2022). These days, the necessity to cyber security in any business is massive since they are absolutely weak to external and internal attacks. Great importance of cyber security in this field with numerous compelling reasons of attacks along with threats will be widely discussed.